TECHNOLOGY FOR ASSESSING THE LEVEL OF DIGITALIZATION OF BUSINESS PROCESSES OF SMALL ENTERPRISES IN THE TRADE SECTOR - CHYHYR, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the issues of digitization of business processes in small businesses in the trade sector, which is currently one of the key factors in increasing competitiveness. It shows that digital transformation for small businesses is no longer an optional innovation but a prerequisite for survival in a dynamic market environment. The purpose of the article is to develop and test a technology for assessing the level of digitization of business processes in small commercial enterprises based on a comprehensive approach that covers both technological and organizational-cultural aspects of digital maturity. The proposed methodology is based on a systematic approach and includes 25 criteria grouped into six blocks: cashier service, customer communication, marketing, analytics, service automation, and IT security. The assessment was carried out on a scale of 0 to 25 points, with three levels of digitalization: low, medium, and high. The study analyzed ten small-format retail chains: KOLO, Nash Krai, Rukavichka, Delvi, Ekonom+, Pingvin/Lecho, Simi, Mi Market (Novus), Fora, and Thrash! This made it possible to identify differences in approaches to digital transformation and highlight the characteristics of each group of companies. According to the analysis results, Mi Market, Fora, and Simi demonstrated the highest level of digitalization, actively using ERP/CRM systems, self-service checkouts, mobile applications, and BI analytics. Their practice shows that comprehensive digitalization is the key to sustainable development even in crisis conditions. An average level of digitalization was found in the KOLO, Nash Krai, Rukavichka, Delvi, and Thrash! chains. They have basic digital tools, but make limited use of analytics, CRM, and omnichannel sales capabilities. This indicates growth potential that can be realized with investment in technological solutions. The group with a low level of digitalization includes Penguin and Ekonom+. They are characterized by the absence of online sales channels, manual accounting, and minimal digital presence. In my opinion, such enterprises are at risk and need urgent implementation of basic automation and CRM systems to maintain their market positions. The practical significance of the study lies in the possibility of using the proposed technology as a strategic management tool. It allows owners and managers to justify investments in digital solutions, identify weaknesses in business processes, and develop targeted development programs. Therefore, it is concluded that digitalization is a key factor in the sustainable development of small businesses in the field of trade. Promising areas for further research include the development of industry standards for digital transformation, assessment of the effectiveness of state support for digitalization, and the search for optimal mechanisms to improve the digital competencies of personnel.